The Influence of Business Ethics Education and Religiosity to Ethical Perception of College Students - Wati, Mirna; Sudibyo, Bambang (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2016)
Abstract: The Influence of Business Ethics Education and Religiosity to Ethical Perception of College Students. The objective of this study is to examine the influence of ethics education, gender, religiosity, and academic performance to the ethical perception of undergraduate. The additional examination was done to know the differences perception between students who have accomplished business ethics course and who have not accomplished business ethics course yet, male and female students, and students who have high GPA and low GPA. The analysis data method uses multiple regression and independent sample t-test. The result indicates that ethics education and academic performance have no significant influence on the ethical perception of college students. On the other hand, religiosity and gender have a significant influence on ethical perception. The result of independent sample t-test indicates that significantly difference between student’s perceptions who have accomplished business ethics course and who have not accomplished yet, likewise between male and female students.Keyword: Ethics Education, Religiosity, Ethical PerceptionAbstrak: Pengaruh Pendidikan Etika Bisnis dan Religiusitas Terhadap Persepsi Etis Mahasiswa Akuntansi. Penelitian ini bertujuan melihat hubungan antara pendidikan etika, gender, religiusitas, dan performa akademik terhadap persepsi etis mahasiswa. Penelitian ini juga ingin membuktikan perbedaan persepsi antara mahasiswa yang sudah atau sedang mengambil mata kuliah etika bisnis dan yang belum, antara mahasiswa laki-laki dan perempuan, serta mahasiswa dengan IPK ≥ 3,3 dan 3,3. Metode analisis data yang digunakan yaitu analisis regresi berganda dan uji beda independent sample t-test. Hasil penelitian menunjukkan bahwa pendidikan etika dan performa akademik tidak berpengaruh signifikan terhadap persepsi etis mahasiswa, berbeda halnya dengan religiusitas dan gender yang memiliki pengaruh yang signifikan. Hasil uji beda menunjukkan perbedaan persepsi etis antara yang sudah atau sedang mengambil mata kuliah etika bisnis dengan yang belum, sama halnya dengan mahasiswa laki-laki dan perempuan.Kata kunci: Pendidikan etika, Religiusitas, Persepsi Etis